Morpho‐physiological variation of Poa alpina L. genetic resources from the Rhaetian Alps, Italy, grown in two altitude‐contrasting sites. (8th September 2014) - Pecetti, L.; Romani, M.; Spoleto, P.; Tosca, A.; Della Marianna, G.; Gusmeroli, F.
Abstract Alpine bluegrass (Poa alpina L.) is common in mountain areas, where it represents a valuable forage resource and is widely used for ecological restoration of disturbed landscapes. This study assessed the variation of germplasm from the Rhaetian Alps, Italy. Both seed production and morphology were examined for potential use in restoration projects and for conservation and selection purposes of local genetic resources. The effects of the ex situ growing site were also assessed in two altitude‐contrasting sites. Individual populations harboured great phenotypic diversity for all traits, including seed yield, while variation among valleys of origin was less manifest. Noticeable site‐specific population yield responses were observed, suggesting that the environment adopted for seed production may steer the choice of materials to be multiplied. The longer vegetative period in the lowland site, combined with environment‐tailored agronomic practices, contributed to better plant growth, seed yield and survival compared to the mountain site, suggesting that seed production of this Alpine species could be feasible in a lowland environment when adequate inputs were provided. One valley (Valchiavenna) displayed high average levels of seed yield and plant vigour across growing sites, indicating its possible value as a source of germplasm suitable for resowing at high altitude.